Altered functional connectivity during hypoglycaemia in type 1 diabetes. Issue 8 (August 2022) - Jacob, Peter; Nwokolo, Munachiso; Cordon, Sally M; Macdonald, Ian A; Zelaya, Fernando O; Amiel, Stephanie A; O'Daly, Owen; Choudhary, Pratik
Behavioural responses to hypoglycaemia require coordinated recruitment of broadly distributed networks of interacting brain regions. We investigated hypoglycaemia-related changes in brain connectivity in people without diabetes (ND) and with type 1 diabetes with normal (NAH) or impaired (IAH) hypoglycaemia awareness. Two-step hyperinsulinaemic hypoglycaemic clamps were performed in 14 ND, 15 NAH and 22 IAH participants. BOLD timeseries were acquired at euglycaemia (5.0 mmol/L) and hypoglycaemia (2.6 mmol/L), with symptom and counter-regulatory hormone measurements. We investigated hypoglycaemia-related connectivity changes using established seed regions for the default mode (DMN), salience (SN) and central executive (CEN) networks and regions whose activity is modulated by hypoglycaemia: the thalamus and right inferior frontal gyrus (RIFG). Hypoglycaemia-induced changes in the DMN, SN and CEN were evident in NAH (all p < 0.05), with no changes in ND or IAH. However, in IAH there was a reduction in connectivity between regions within the RIFG (p = 0.001), not evident in the ND or NAH groups. We conclude that hypoglycaemia induces coordinated recruitment of the DMN and SN in diabetes with preserved hypoglycaemia awareness which is absent in IAH and ND. Changes in connectivity in the RIFG, a region associated with attentional modulation, may be key in impaired hypoglycaemia awareness.